Supply Chain Management of Ready-Mix Concrete in Large-Scale Projects and Short Time (Case Study: Construction of Yogyakarta International Airport, Kulonprogo) - Ery Supratomo; Jati Utomo Dwi Hatmoko; Ferry Hermawan (Eduvest - Journal of Universal Studies, 2025)
The Yogyakarta International Airport Project, valued at IDR 5.8 trillion, demands an exceptionally high daily supply of ready-mix concrete—approximately 7,000 m³—within a tight timeframe of only eight effective months. Given that concrete work constitutes 20% of the total project value, an efficient and reliable supply chain becomes essential. This research aims to simulate and analyze supply chain management (SCM) strategies specifically for the procurement of ready-mix concrete, with the objective of identifying the most efficient supply pattern to ensure both quality and timely delivery. Using production capacity analysis and SCM simulation, the study reveals that existing batching plants on and around the site can only meet a daily capacity of 5,272 m³. To bridge the gap, a self-managed batching system is proposed, which involves establishing three new batching plants at the project site, each with a 1,000 m³/day capacity, while centralizing raw material procurement under the project team for quality control. The simulation results show that the self-management model is more cost-effective, reducing the price of ready-mix concrete from IDR 936,833.00 to IDR 895,392.00 per m³, yielding a cost efficiency of IDR 41,441.00 per m³. These findings highlight the importance of SCM optimization and self-management strategies in large-scale infrastructure projects for enhanced cost and quality control.